EVENT MARKETING: HOW SOCIAL MEDIA START-UP SEETIES APP ACQUIRES USERS IN INDONESIA - Primadi Wahyuwidagdo, S.E., MBA; Iqbal Fachreza (Management and Leadership Study Programme, 2018)
This study explores the event marketing as apart of marketing mix practiced by Seeties App, a social media start-up, to acquire users in Indonesia. Event marketing is a part of marketing strategy taken by Seeties App to acquire potential users in Indonesia. This is a case study research and exploratory qualitative research. We use primary and secondary data. The primary data is gathered by; interview the Seeties’s management in Indonesia and observation the process as participatory observation. The, secondary data is acquired through company’s data, and third parties. The result of this study shows that the event marketing strategies used by Seeties shows that they do not have competitive advantage. By the VRIO analysis, we can conclude that the strategy has competitive parity. The strategy is valuable but not rare and inimitable. The failure to exploit the strategies, possibly lead the company to competitive disadvantage. Even though this marketing strategy gain no competitive advantage. However, this event marketing is very efficient related to company weakness and lack of strength as in startup phase. The analysis by using TOWS matric, the company shows that they are capable to minimize the threat and weakness even though the company is struggling exploit opportunity. The company seeks the higher chances of marketing tools give exact number of new user rather than using tools that may highly cost but less of impact to the company.